2002
DOI: 10.1139/v02-034
|View full text |Cite
|
Sign up to set email alerts
|

Biocatalytic oxidation of 4-vinylphenol by Nocardia

Abstract: Nocardia species NRRL 5646 stereospecifically hydrates 4-vinylphenol (15) to S-1-(4'-hydroxyphenyl)ethanol (17), and further oxidizes 17 to 4'-hydroxyacetophenone (18). Labeled metabolites 17 and 18 obtained from incubations in D2O and H218O support initial enzymatic tautomerization of 15 to a reactive quinone methide (16), which adds water in the first reaction. Commitment to catalysis is high in the hydration reaction, while the alcohol dehydrogenation reaction appears to be reversible. The stereochemical fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…A soluble form of nitric oxide synthase (NOS NOC ), 13 carboxylic acid reductase, 14 aryl aldehyde oxidoreductase, 15 aldehyde reductase, 16 guanylate cyclase, 17 and ornithine transcarbamoylase 18 have all been characterized in this organism. Activities for Nocardia cyclohydrolase I, sepiapterin reductase, vinylphenol hydratase, 19 hydroxyethylphenol oxidoreductase, 19 and vanillate decarboxylase are all under investigation in our laboratory.…”
Section: Resultsmentioning
confidence: 99%
“…A soluble form of nitric oxide synthase (NOS NOC ), 13 carboxylic acid reductase, 14 aryl aldehyde oxidoreductase, 15 aldehyde reductase, 16 guanylate cyclase, 17 and ornithine transcarbamoylase 18 have all been characterized in this organism. Activities for Nocardia cyclohydrolase I, sepiapterin reductase, vinylphenol hydratase, 19 hydroxyethylphenol oxidoreductase, 19 and vanillate decarboxylase are all under investigation in our laboratory.…”
Section: Resultsmentioning
confidence: 99%
“…In this study it has been shown that Nocardia is capable of producing 1-(4-hydroxyphenyl)ethanol and 4-hydroxyacetophenone when incubated with 4-vinylphenol. The authors hypothesised that in this conversion a quinone methide intermediate might be involved (Lee & Rosazza, 2002). 07.154,07.164,07.243 and 07.234] No data have been submitted for any of these five candidate flavouring substances.…”
Section: Vinyl-and Alkoxy-substituted Phenolmentioning
confidence: 99%
“…The authors hypothesised that in this conversion a quinone methide intermediate might be involved (Lee & Rosazza, 2002).…”
Section: Phenols With Alkoxy- Alkenyl-or Ketonic Ring Substituentsmentioning
confidence: 99%
“…In this study it has been shown that Nocardia is capable of producing 1-(4-hydroxyphenyl)-ethanol and 4-hydroxyacetophenone when incubated with 4-vinylphenol. The authors hypothesised that in this conversion a quinone methide intermediate might be involved (Lee & Rosazza, 2002).…”
Section: Ester Hydrolysismentioning
confidence: 99%